UJI BERBAGAI MEDIA TANAM DAN PEMBERIAN AIR KELAPA MUDA TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis quineensis.Jacq) Di MAIN NURSERY - Marlina, Gusti (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2018)
Success in oil palm cultivation is greatly influenced by the procurement of seedsand media. In addition to procuring seeds and good media, the use of ZPT also supports the success of nurseries. Use of young coconut water in nurseries. Young coconut water which contains a lot of growth regulators (ZPT) which can stimulate germination and growth of oil palm seedlings. The purpose of this study was to determine the various planting media tests and the provision of young coconut water to the growth of oil palm seedlings (Elaeis quineensis. Jacq) in the main nursery. This study uses Factorial Randomized Block Design (RBD) which consists of 2 factors, the first factor is the factor (M) of planting media which consists of 5 levels, namely: M0 = soil (control), M1 = Land + Sand (2: 1), M2 = Land + Sand + Tea grounds (2: 1: 1), M3 = Land + Sand + Rice Husk (2: 1: 1), M4 = Land + Sand + Cowhide Fertilizer (2: 1: 1), and thesecond factor is (A) giving young coconut water which consists of 4 levels, namely: A0 = without giving young coconut water (control), A1 = giving young coconut water 20%, A2 = giving 40% young coconut water, A3 giving coconut water young 60%. Data were analyzed statistically using analysis of variance and further tested for Honest Real Difference 5%. The results showed that the treatment of various planting media and giving young coconut water interactively did not significantly affect all observation parameters, but the best results were shown in the treatment of M1A0 in observing the height of the seedlings (cm) as high as 47.60 cm and the base diameter of the stem of 3.45 cm2. as well as the main influence of various planting media and the provision of young coconut water is not real in all parameters of observation. Keywords: growing media ,oil palm, main nursery, ZPT